Characterisation of end groups of hydroxy-functionalised scl-PHAs prepared by transesterification using ethylene glycol. (November 2022) - Mai, Jingjing; Chan, Clement Matthew; Colwell, John; Pratt, Steven; Laycock, Bronwyn
Highlights: Transesterification of PHBVs of low (1 mol%) and high (63mol%) HV content. Characterization of hydroxy‑terminated PHBVs M n > 20 kDa) and reaction by-products. A portion of commercial & laboratory derived PHBVs are dicarboxylic acid-terminated. Abstract: Polyhydroxyalkanoates (PHAs) are a family of biodegradable polyesters with good potential in applications ranging from packaging to implants. The synthesis of block copolymers based on PHAs is one approach to tailoring these physical properties. This work considers the transesterification and end-group characterisation of hydroxy‑terminated PHAs for the chemical synthesis of PHA-based block copolymers. There is currently incomplete knowledge of the relative amounts of the different end-groups in the as-produced materials. Further, the reported hydroxy‑terminated PHAs have relatively low molecular weights ( M n < 4 kDa); hydroxy‑terminated PHAs of intermediate molecular weights ( M n > 20 kDa) - which are more favourable as building blocks for industrially relevant high molecular weight PHA - have not yet been fully characterised for use in such applications, to our knowledge. Here, a more comprehensive strategy for the preparation and characterisation of hydroxy‑terminated PHAs of intermediate molecular weights was applied. Hydroxy-functionalised PHAs were produced via transesterification of poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) of differing 3HV contents and with narrow compositional distribution, followed by purification through solvent processing. The functionalised PHAs and reaction by-products were then characterised using FT-IR, 1 H-NMR, 13 C-NMR, 31 P-NMR, GPC and DSC analyses, allowing the determination of the nature and distribution of the end groups. It was found that transesterification does indeed generate both primary and secondary hydroxyl end-groups, while original PHBV materials (PHBpre-sol ) had only secondary hydroxyl end groups present. 41% of hydroxy‑functionalised PHBV (PHBtr-sol- D ) were likely terminated with either crotonic groups or carboxylic acids. Further, the analysis showed that a proportion of commercial and laboratory derived PHBVs (PHBpre-sol and PHBVpre-sol ) was likely dicarboxylic acid-terminated.